2020
DOI: 10.1073/pnas.2016049117
|View full text |Cite
|
Sign up to set email alerts
|

HOS15 is a transcriptional corepressor of NPR1-mediated gene activation of plant immunity

Abstract: Transcriptional regulation is a complex and pivotal process in living cells. HOS15 is a transcriptional corepressor. Although transcriptional repressors generally have been associated with inactive genes, increasing evidence indicates that, through poorly understood mechanisms, transcriptional corepressors also associate with actively transcribed genes. Here, we show that HOS15 is the substrate receptor for an SCF/CUL1 E3 ubiquitin ligase complex (SCFHOS15) that negatively regulates plant immunity by destabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 103 publications
(135 reference statements)
1
36
0
1
Order By: Relevance
“…Furthermore, HOS15 interacts with and degrades OST1, thereby regulating the desensitization of the ABA signaling pathway (Ali et al, 2019). In line with these reports, we have also shown that HOS15 interacts with the SCF-CUL4-E3 ligase complex to repress the plant immune system by negatively regulating NPR1, a pathogen-responsive positive regulator (Shen et al, 2020). Despite all these multiple functions, the role of HOS15 in senescence remains unknown.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, HOS15 interacts with and degrades OST1, thereby regulating the desensitization of the ABA signaling pathway (Ali et al, 2019). In line with these reports, we have also shown that HOS15 interacts with the SCF-CUL4-E3 ligase complex to repress the plant immune system by negatively regulating NPR1, a pathogen-responsive positive regulator (Shen et al, 2020). Despite all these multiple functions, the role of HOS15 in senescence remains unknown.…”
Section: Introductionsupporting
confidence: 79%
“…High Expression of Osmotically Responsive Genes 15 (HOS15), a WD40 repeat protein, has multiple molecular functions, including the regulation of plant growth and development, cold stress signaling, flowering time determination, abscisic acid (ABA) signaling, response to drought stress, and pathogen response (Zhu et al, 2008;Park et al, 2018a;Ali et al, 2019;Mayer et al, 2019;Park et al, 2019;Shen et al, 2020). During cold stress, HOS15 interacts with and promotes proteasomal degradation of histone deacetylase 2C (HD2C).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the discovery of common targets or susceptibility genes for pathogens in crop plants could now be a very important focus. In fact, pathogens sharing the same plant targets have been frequently reported (Ali and Yun, 2020; Park et al ., 2019; Ray et al ., 2019; Shen et al ., 2020). Our study provides an approach to develop highly resistant plants against multiple pathogens by editing only a single gene.…”
Section: Discussionmentioning
confidence: 99%
“…Functional deficiencies in CSN result in strong pleiotropic effects including auxin-insensitivity (Dohmann et al ., 2008), constitutive activation of PSR (Walia et al, 2020), and impaired JA-defenses accompanied by elevated PR1 transcripts (Hind et al ., 2011), thus revealing strong parallel with ipk1-1 or itpk1-2 defects. Rice SPX4, SNC1 or NPR1 stabilities are monitored by CRL functions placing molecular implications of IPK1/ITPK1 on defense outcomes via CSN-CRL dynamics (Gou et al ., 2012; Ruan et al ., 2019; Ried et al ., 2019; Shen et al ., 2020). These indications lead us to advocate that between the investigated InsP-kinases, IPK1 and ITPK1 have acquired unique localized roles that impinge on central cellular machineries impacting multiple signaling networks.…”
Section: Discussionmentioning
confidence: 99%